Understanding professional challenges and coping strategies within the resilience process that support teacher well-being. - Isabelle Krummenacher; Tina Hascher; Caroline Mansfield; Susan Beltman; Julia Mori; Irene Guidon (Frontline Learning Research)
Teaching is an immensely complex profession with a variety of challenges. This qualitative study explores challenges that teachers face and how teachers cope with these challenges to maintain their well-being. The study is based on the Aligning Well-being and Resilience in Education (AWaRE) model and aims at identifying relevant teacher challenges and coping strategies to contribute to an evidence-based understanding of well-being and resilience within the teaching profession. We analysed teachers’ coping strategies in challenging situations based on semi-structured interviews with N=29 teachers from schools in Switzerland. Results showed that social factors at diverse levels such as school management, parent interaction and class composition represent the central contextual challenges, while social support systems from school management and colleagues and cooperation among teachers are significant contextual resources. Problem-solving was used as a frequent coping strategy. The results of this study provide implications for understanding the ways to support a successful resilience process among teachers and designing interventions to enhance teachers’ resilience.